Adults With Idiopathic Scoliosis Diagnosed at Youth Experience Similar Physical Activity and Fracture Rate as Controls. Issue 7 (1st April 2017) - Diarbakerli, Elias; Grauers, Anna; Danielsson, Aina; Gerdhem, Paul
Abstract : Study Design: Cross-sectional. Objective: To describe physical activity level and fracture rates in adults with idiopathic scoliosis, diagnosed before maturity, and to compare with a control group. Summary of Background Data: A previous study found a lower level of sporting activities in adults treated for idiopathic scoliosis compared with controls. Other studies have shown a lower bone mass in adults with idiopathic scoliosis compared with controls. Methods: One thousand two hundred seventy-eight adults (aged 18–71 yr) with idiopathic scoliosis and 214 controls (aged 18–70 yr) were included and answered the International Physical Activity Questionnaire – Short Form (IPAQ-SF) and questions about previous fractures. The three scoliosis treatment groups (untreated n = 360, brace n = 460, and surgically treated n = 458) were compared. Furthermore, a comparison based on onset (juvenile n = 169 or adolescent n = 976) was performed. Achieved weekly moderate activity level and metabolic equivalent task (MET) minutes/week were assessed for patients and controls. Statistical comparisons were made with analysis of covariance with adjustments for age, body mass index, and sex. Results: The proportion achieving weekly moderate activity level was 962 out of 1278 for individuals with idiopathic scoliosis (75%) and 157 out of 214 (73%) for controls ( P  = 0.40). The scoliosis patients reported 2016 MET-minutes/week (median value) and the controls 2456 ( P  = 0.06). Fracture rates did not differ ( P  = 0.72). Fewer surgically treated individuals achieved moderate activity level ( P  = 0.046) compared with the untreated and the previously braced individuals. No difference was seen regarding MET-minutes/week ( P  = 0.86). No differences were seen between individuals with a juvenile onset compared with individuals with an adolescent onset (all P ≥ 0.05). Conclusion: Adults with idiopathic scoliosis have similar physical activity level and do not sustain more fractures compared with controls. Adults with surgically treated idiopathic scoliosis have slightly lower physical activity level than previously braced and untreated patients. Onset of idiopathic scoliosis does not affect physical activity level. Level of Evidence: 2